Resilience and Adaptation: Yukon River Watershed Contaminant Risk Indicators - Lawrence Duffy; La’Ona De Wilde; Katie Spellman; Kriya Dunlap; Bonita Dainowski; Susan McCullough; Bret Luick; Mary van Muelken (Scientifica)
River watersheds are among the most complex terrestrial features in Alaska, performing valuable ecosystem functions and providing services for human society. Rivers are vital to both estuarine and aquatic biota and play important roles in biogeochemical cycles and physical processes. The functions of watersheds have been used as vulnerability indicators for ecosystem and socioeconomic resilience. Despite a long history of human activity, the Yukon River has not received the holistic and interdisciplinary attention given to the other great American river systems. By using hypothesis-based monitoring of key watershed functions, we can gain insight to regime-shifting stresses such as fire, toxins, and invasive species development. Coupling adaptive risk management practices involving stakeholders with place-based education, especially contaminants and nutrition related, can maintain resilience within communities. The Yukon watershed provides a broadscale opportunity for communities to monitor the environment, manage resources, and contribute to stewardship policy formation. Monitoring keystone species and community activities, such as citizen science, are critical first steps to following changes to resiliency throughout the Yukon watershed. Creating a policy environment that encourages local experimentation and innovation contributes to resilience maintenance during development-imposed stress.